The Relationship of Motivation and Neurocognition with Functionality in Schizophrenia: A Meta-analytic Review. - Najas-Garcia, Antonia; Gómez-Benito, Juana; Huedo-Medina, Tania B. (Community Mental Health Journal, 2018)
The role that neurocognition plays in functionality in schizophrenia has been widely examined, although in recent years increasing attention has been paid to the influence of motivation instead. This study provides a review of the relationship of neurocognition and motivation with functionality in schizophrenia, taking into account objective/subjective functionality assessment, demographic variables, and the different terms used when referring to motivation. A search of electronic databases identified 34 studies that met the inclusion criteria for review. Correlation coefficients between motivation and functionality and between neurocognition and functionality were extracted. For a better understanding, potential moderator variables were also extracted. Meta-analysis showed that both motivation and neurocognition assessments were strongly associated with functioning, with correlations between motivation and functional outcomes being stronger. However, more than three-quarters of the variance in outcome remained unexplained by the moderating factors examined. The paper concludes with recommendations for clinical practice and future research.